Perching behaviour and disturbance during sleep in three hybrids of broiler chicken (Gallus gallus domesticus) - Wedin, Maja (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
The aim of broiler chicken production is to breed chickens with high growth rate and muscle/bone ratio. However, this selection has affected the physiology of the broilers and as a result broilers display a physique that inhibits them in executing behaviours that they are motivated to perform. Hybrids of reduced growth rate seem to be less impeded by their physique than faster growing hybrids. Perching is a natural behaviour for chickens and sleeping undisturbed is important for the welfare of the individual. When sleeping on the floor, broilers risk being disturbed as individuals that are awake might step on them, resulting in reduced welfare for the startled chicken. EU-organic regulations state that the choice of hybrid in EU-organic production should prevent animal suffering. It is therefore important to study how different hybrids vary in perching behaviour and disturbance of sleeping chickens. Hence, this study aimed to compare perching behaviour as well as disturbance during sleep in three hybrids of different growth rate. Three hybrids differing in growth rate were used in this study; Ross 308, Rowan Ranger and Hubbard CYJA57, 100 birds per hybrid. The hybrids were housed together in one flock (stocking: 1.84 chickens/m2 or 8.19kg/m2 at slaughter) under EU-organic conditions and provided with perches of three heights (20, 40 and 70 cm). There was always plenty of perch space during the study. Observations were performed by group scan during photophase as well as scotophase and by focal bird observation. Significance was calculated with Chi square test, Yates correlation Chi square test or Student’s T-test. Ross chickens perched significantly less than Hubbards and Rowan Rangers during photophase and scotophase (P<0.001) even though there was no significant difference in sleeping behaviour during photophase (P>0.1). Ross utilized only the lowest perches while the other hybrids perched on all heights. Disturbance of sleeping chickens was not significantly different between hybrids but Hubbards tended to disturb sleeping birds more than Ross chickens did. Furthermore, males were significantly more prone to perform disturbance than females (P<0.05). Hubbards were at greater risk than Ross chickens to be recipients of disturbance (P<0.05) and Rowan Rangers showed a tendency to receive more disturbance than Ross. Being the recipient of disturbance was not affected by gender. As the Ross chickens perched to a lesser extent than the other two hybrids, and as they only perched on the lowest perches, it is probable that they experienced a reduced welfare in comparison to the other hybrids. However, Ross chickens were less disturbed during sleep which indicates a higher welfare in this aspect. Due to the results in the present study this paper argues that, in order to comply with EU-organic regulations, Hubbard CYJA57 or Rowan Ranger should be favoured over Ross 308 as these hybrids attain a higher welfare when compared to Ross.